Fermented cassava waste and its utilization in broiler chickens rations - ., Supriyati (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Cassava waste is a by-product of cassava flour industry and its amount is increasing following the increasing of cassava flour industry. Its utilization as a feedstuff, is limited by its low protein content. The cassava waste is only utilized as the energy source. One of the alternative technology in improving the utilization of cassava waste as a feedstuff, by improving the nutritive value through fermentation process. Fermentation was carried out by solid substrate fermentation using Aspergillus niger as an inoculant and mixing with urea and ammonium sulphate as inorganic nitrogen sources. The nutritive value of the product was evaluated by feeding trial using 144 âShaver Stabroâ strain 3 days old chicks with 3 treatments i.e. 0 (control), 5.0 and 10.0% fermented cassava waste. The results showed that the true protein content of fermented cassava increased from 2.2 to 18.4%. The inclusion of fermented cassava waste up to 10% in chicken broiler ration for 4 weeks feeding did not affect the feed consumption, bodyweight gain, FCR, weight of liver and gibblets. All parameter results from 10% inclusion were not significantly different (P>0.05) with the control (0% inclusion). Â  Key words: Fermentation, cassava waste, utilization, broiler chickens